Association between Leptin, Adiponectin Levels, and Nutritional Status in Children with Down Syndrome - Utari, Agustini; Panunggal, Damianus Galih; Rahardjo, Tithasiri Audi; Lestari, Wiwik; Cayami, Ferdy K; Winarni, Tri Indah (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: Children with Down Syndrome (DS) have been associated with obesity. Leptin and adiponectin were also significant predictors of obesity and its comorbidity in DS. However, there was limited data regarding leptin and adiponectin in children with DS, particularly who were undernutrition. This study aimed to seek the role of leptin levels, adiponectin levels, and nutritional status in children with DS. Methods: This cross-sectional study was conducted on 40 children with DS aged 1 - 5 years. Height and weight were measured, and then the growth was interpreted using a DS growth chart. The Weight for Height Z-Score (WHZ) and Height for Age Z-Score (HAZ) were determined, and Mid-Upper Arm Circumference (MUAC) was measured. Leptin and adiponectin serum were analyzed using the enzyme-linked immunosorbent assay (ELISA) method. Mann-Whitney test was done to compare leptin and adiponectin levels in normal and wasted groups, while Spearman’s analysis was carried out to correlate laboratory results and anthropometric parameters. Results: Forty children participated (23 males, 17 females) with a median age was 25.5 months. Ten out of 40 children with DS (25%) were wasted and leptin was significantly lower in wasted compared to normal children. In addition, leptin was significantly correlated with WHZ (r = 0.415; p = 0.008), and MUAC (r = 0.427; p = 0.006), while adiponectin did not significantly correlate with those anthropometric variables in both wasted or non-wasted groups. Conclusion: Leptin is associated with WHZ and MUAC, and it decreases in wasted children with DS.